Respon Pemerintah Lokal Terhadap Gerakan Sosial Politik Petani di Kanagarian Mungo Kabupaten 50 Kota Provinsi Sumatera Barat - Dewi Anggaraini (Al-Risalah, 2011)
The Agricultural conflict which delivers farmers strikes has already colored the socio-political condition in Indonesia since colonialism era till reformation era. One of Frmer’s movements still happens in mungo village. Luak sub-district, 50 kota district, west Sumatra Province. On that village live 300 families who stay on claim to own the land belongs to Indonesia agriculture department and protected by using-rig ht certivicate number 03.05.01.4.00005. The farmers denied the certivicate and claim that they have more rights to that land based on rental agreement dutch government in 1918 and there has been any changing on the agreement, which means that land (according to the farmers) is not included into erfpaccht verponding lands which became the foundation the publidhing of using-right certivicate on behalf of agriculture department. This farmer movement was responded by the local government b many policies which cannot be accepted by farmers because the policies made without consulting to farmers . the responses of local govertment categorized into: local government of west-sumatra province, 50 kota district, luak sub-district, and mungo village, with different policies.